Sustainable Innovation and Resilience in Management: The Interplay Between AI, ICTs, and Green Entrepreneurship in the Digital Age - Raghvendra,; Saxena, Tulika; Karki, Mahima; Pravesh, Jag; Chauhan, Bipin (Nepalese Journal of Management Science and Research, 2025)
The integration of Artificial Intelligence (AI), Information and Communication Technologies (ICTs), and green entrepreneurship is reshaping modern management practices, driving sustainable innovation and enhancing resilience. This paper explores the synergistic relationship between these technologies and environmentally-focused entrepreneurship, examining their role in advancing sustainability and organizational resilience. AI and ICTs empower businesses to optimize resources, reduce environmental impact, and foster eco- friendly innovations. Green entrepreneurship, in turn, contributes to the circular economy and sustainable development goals (SDGs). Through case studies and theoretical analysis, this paper investigates how these forces collectively contribute to sustainable business models, while addressing challenges such as energy consumption and the digital divide. The findings highlight the transformative potential of AI, ICTs, and green entrepreneurship in promoting long-term resilience and sustainability in the digital era.